STRATEGI PENGEMBANGAN AGRIBISNIS KOPI ROBUSTA UNTUK MENDUKUNG PEMASARAN BIJI KOPI ROBUSTA DI KABUPATEN CIAMIS - Saepul Aziz; Sudrajat Sudrajat; Ivan Sayid Nurahman; Rian Kurnia (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2021)
Robusta Cofee the plantation commodities with sufficient potential for development in Ciamis district. Robusta coffee production in Ciamis district experienced an increase of 4.95 percent in 2019 from the average coffee production in 2018 amounted to 4.07 percent, this condition indicates that the plantation coffee in Ciamis district became one of the commodities that was pretty  potensial to be developed. Therefore we need a good strategy in order to  perkebunan robusta coffee can provide great benefits for an increased community welfare in Ciamis district in particular. The aim of this study is to measure the potential of Robusta coffee as a leading sector in plantation commodities Ciamis district, analyze the factors internal and external to the Development of robusta coffee and coffee penegmbangan determine strategic priorities robusta. This research uses a survey method. Location research has been retained earnings purposive Panawangan subdistrict. The number of samples taken is 181 people. The results showed that the base area of robusta coffee was based on the highest indicator of production in Ciamis district is Panawangan district with an LQ value of 3.65, it means that every 1 part of robusta coffee production will be  used to meet the needs of Panawangan district and the remaining 2.65  part to meet the demand for robusta coffee commodities in other regions. Analysis of the QSPM matrix shows that the right strategy is an alternative to strategy with the highest total score of 6.38. The chosen strategy is farming development robusta coffee through the use of technological innovations in the area of cultivation potential and  developing a robusta coffee marketing network. With this strategy it is expected to be able to solve problems in robusta coffee agribusiness development in  the districts of Ciamis